PENGARUH KEPEMIMPINAN, BUDAYA ORGANISASI DAN KEADILAN PROSEDURAL TERHADAP KOMITMEN ORGANISASI (Studi Pegawai Seketariat Daerah Pemprov.DKI Jakarta dan Pemprov.Sumut) (Civic Education Program, Universitas Negeri Semarang, 2018)
Organizational Commitment can be referred to three emplooyee’s characteristics, namely theirself belonging to organization, their willingness to work for organization, and their acceptenceof the values and the objectives of the organization. The organizational commitment is influenced by many factors, like, leadership, organizational culture, attitude and personality, motivation, procedural justice and others. This study was intended to investigate the effect of leadership, organizational culture, and procedural justice on organizational commitment of Secretarial Office employees of DKI and Sumut Provinces. The data was collected through survey to 80 emplooyees who were selected randomly from the employees of echelon III Secretarial Office DKI and Sumut Provinces.The data were then analyzed by path analysis technique. Result indicated that organizational commitment was directly affected by leadership and procedural justice but not by organizational culture. In others words leadership and organizational justice affects the organizational commitment. The findings imply that the employees commitment can be improved through the improvement of leadership and organizational justice. However, others variables can be put into consideration in the future research to find out more information related to the variable.